ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI CENGKEH DI KECAMATAN KUWUS BARAT KABUPATEN MANGGARAI BARAT - Ferianus Habun; Wiendiyati Wiendiyaty; Ida Nurwiana (Buletin Ilmiah Impas, 2022)
Research on The Analysis of Factors Influencing the Production of Clove Farming (Syzigium Aromaticum) in West Kuwus District West Manggarai Regency Aims to analyze factors that affect the production of clove farming and to analyze the production rate of clove farming in West Kuwus District West Manggarai Regency. Field research was conducted during September 2020 in the West Kuwus Subdistrict area of West Manggarai Regency. Data used are primary and secondary data. The determination of respondents is done using a simple random sampling method. The number of samples taken amounted to 15% of the total population of 180 people so that 35 respondents were clove farmers. Data analysis using regression through Cobb-Douglas production function approach. The results showed that, factors that have a positive and significant effect on the production of clove plants are plant age, fertilizer use, and number of plants. While factors of crop area, and the use of pesticides have a negative relationship and have no significant effect on the production of clove crops. Furthermore, the use of labor has no significant effect on clove production but has a positive relationship. These results indicate that the addition of labor at a certain time especially at the time of harvest can increase the production of clove crops. The income of clove farming is largely determined by the age of the plant and the amount of plant ownership. The lowest income per plant in the 5 - 10 year plant age group is Rp 175 thousand and the highest at the age of plants over 25 years is Rp 1,625,000,-. Income by crop ownership is the lowest of Rp 3.500.000,- with the ownership of as many as 20 trees in the age group of 5 - 10 years; and the highest amount of Rp 339.250.000,- with the ownership of 230 trees in the age group of 21 - 25 years.